Cellular surface plasmon resonance-based detection of anti-HPA-1a antibody glycosylation in fetal and neonatal alloimmune thrombocytopenia - Szittner, Zoltán; Bentlage, Arthur E. H.; Temming, A. Robin; Schmidt, David E.; Visser, Remco; Lissenberg-Thunnissen, Suzanne; Mok, Juk Yee; van Esch, Wim J. E.; Sonneveld, Myrthe E.; de Graaf, Erik L.; Wuhrer, Manfred; Porcelijn, Leendert; et al. (Frontiers in Immunology, 2023)
Fetal and neonatal alloimmune thrombocytopenia (FNAIT) can occur due to maternal IgG antibodies targeting platelet antigens, causing life-threatening bleeding in the neonate. However, the disease manifests itself in only a fraction of pregnancies, most commonly with anti-HPA-1a antibodies. We found that in particular, the core fucosylation in the IgG-Fc tail is highly variable in anti-HPA-1a IgG, which strongly influences the binding to leukocyte IgG-Fc receptors IIIa/b (FcγRIIIa/b). Currently, gold-standard IgG-glycoanalytics rely on complicated methods (e.g., mass spectrometry (MS)) that are not suited for diagnostic purposes. Our aim was to provide a simplified method to quantify the biological activity of IgG antibodies targeting cells. We developed a cellular surface plasmon resonance imaging (cSPRi) technique based on FcγRIII-binding to IgG-opsonized cells and compared the results with MS. The strength of platelet binding to FcγR was monitored under flow using both WT FcγRIIIa (sensitive to Fc glycosylation status) and mutant FcγRIIIa-N162A (insensitive to Fc glycosylation status). The quality of the anti-HPA-1a glycosylation was monitored as the ratio of binding signals from the WT versus FcγRIIIa-N162A, using glycoengineered recombinant anti-platelet HPA-1a as a standard. The method was validated with 143 plasma samples with anti-HPA-1a antibodies analyzed by MS with known clinical outcomes and tested for validation of the method. The ratio of patient signal from the WT versus FcγRIIIa-N162A correlated with the fucosylation of the HPA-1a antibodies measured by MS (r=-0.52). Significantly, FNAIT disease severity based on Buchanan bleeding score was similarly discriminated against by MS and cSPRi. In conclusion, the use of IgG receptors, in this case, FcγRIIIa, on SPR chips can yield quantitative and qualitative information on platelet-bound anti-HPA-1a antibodies. Using opsonized cells in this manner circumvents the need for purification of specific antibodies and laborious MS analysis to obtain qualitative antibody traits such as IgG fucosylation, for which no clinical test is currently available.